Endocrine Regulation of Extra-skeletal Organs by Bone-derived Secreted Protein and the effect of Mechanical Stimulation - Du, Yuxiang; Zhang, Lingli; Wang, Zhikun; Zhao, Xuan; Zou, Jun (Frontiers in Cell and Developmental Biology, 2021)
Bone serves as the support for body and provide attachment points for the muscles. The musculoskeletal system is the basis for the human body to complete exercise. Studies believe that bone is not only the basis for constructing structures, but also participates in the regulation of organs outside bone. The realization of this function is closely related to the protein secreted by bone. Whether bone can realize their positions in the human body is also related to their secretion. Bone-derived proteins provide a medium for the targeted regulation of bones on organs, making the role of bone in human body more profound and concrete. Mechanical stimulation effects the extra-skeletal organs by causing quantitative changes in bone-derived factors. When bone receives mechanical stimulation, the nichle of bone responds, and the secretion of various factors changes. However, whether the proteins secreted by bone can interfere with disease requires more research. In this review article, we will first introduce the important reasons and significance of the in-depth study on bone-derived secretory proteins, and summarize the locations, structures and functions of these proteins. These functions will not only focus on the bone metabolism process, but also be reflected in the cross-organ regulation. We specifically explain the role of typical bone-derived secretory factors such as osteocalcin (OCN), osteopontin (OPN), sclerostin (SOST) and fibroblast growth factor 23 (FGF23) in different organs and metabolic processes, then establishing the relationship between them and diseases. Finally, we will discuss whether exercise or mechanical stimulation can have a definite effect on bone-derived secretory factors. Understanding their important role in cross-organ regulation is of great significance for the treatment of diseases, especially for the elderly people with more than one basic disease.